Calidad de cuidado de enfermería según dimensiones, servicio de emergencia. Hospital de Apoyo Chepén, 2019 - Aguilar Castillo, Nelly Mercedes (2020)
This study aims to determine the level of quality of nursing care according to dimensions: accessibility, explicit and facilitates, comfort, anticipation, trust relationship, monitoring and follow-up, emergency service. Chepén Support Hospital, 2019. The quantitative method, descriptive design, was used. The sample consisted of 113 patients between the ages of 18 and 75 years of age, the instrument used was Care-Q (Caring Assessment Instrument) by Patricia Larson (2008). The data were organized in Excel and processed in SPSS version 25. The results obtained were that: The quality of nursing care is high with 49.6%, medium with 37.2% and low with 13.3%. And the level of quality of nursing care according to the dimensions: Accessibility presented high level 49.6%, medium level 36.3% and low level with 14.2%; Explicit and facilitates medium level 38.9%, high level 33.6 and low level 27.4%; It comforts medium level 45.1%, high level 37.2% and low level. 17.7%; Anticipates, high level 50.4%, medium level 27.4% and low level 22.1%; Maintains a 49.6% high level, 28.3% medium level and 22.1% low level and finally monitors and monitors 69.9% high level, 28.0% medium level and 7.1% low level